Pengaruh Campuran Bahan Bakar Bensin Dan Etanol Terhadap Prestasi Mesin Bensin - Yolanda J. Lewerissa (Industrial Engineering Study Program, Pattimura University, 2011)
This research done is to know engine performance at benzine fuel mixture and ethanol yielded by engine Enduro XL. To know engine performance hence done [by] calculation effective power, fuel usage, usage of specific fuel, mass flow rate actually, theoretical mass flow rate, comparison of fuel atmosphere, volumetric efficiency, thermal efficiency. As well as research done at condition of five various revolution with constant payload and fuel applied only one types that is premium ( benzine) with ethanol 0%, 5%, 10%, 15% and 20%. From result of assaying that average of energy? power for mixture fuel bigger than pure premium, existence of increase of usage of fuel along with the increasing of revolution because bigger benzine fuel mixture octane number and ethanol compared to pure benzine so that inflammable, fuel mixture excelsior hence increasingly low comparison of atmosphere with fuel material hence baking happened unable to perfect admission into combustion chamber, efficiency thermal yielded by mixture fuel average of lower than except to pure premium of mixture 5 %. For the purpose engine performance using higher mixture fuel from engine performance using premium fuel. consumption of Fuel for bigger mixture fuel compared to pure premium fuel.